2002
DOI: 10.1097/00005768-200208000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-methods resistance training increases power and strength of young and older men

Abstract: Although the results of this study confirm age-related reductions in muscle strength and power, the older men did demonstrate similar capacity to young men for increases in these variables via an appropriate periodized resistance-training program that includes rapid, high-power exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
18

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(129 citation statements)
references
References 26 publications
8
103
0
18
Order By: Relevance
“…It was surprising that despite a well-controlled exercise program the true changes in the most of measured parameters were difficult to detect. The present study confirms that mixed strength training methods could affect more clearly neuromuscular performance and its explanatory mechanisms than power training alone as Newton et al (2002) and Lyttle et al (1996) have demonstrated. Thus, future training studies should focus on developing new parameters besides the conventionally employed MVC and RFD.…”
Section: Perspectivessupporting
confidence: 87%
See 1 more Smart Citation
“…It was surprising that despite a well-controlled exercise program the true changes in the most of measured parameters were difficult to detect. The present study confirms that mixed strength training methods could affect more clearly neuromuscular performance and its explanatory mechanisms than power training alone as Newton et al (2002) and Lyttle et al (1996) have demonstrated. Thus, future training studies should focus on developing new parameters besides the conventionally employed MVC and RFD.…”
Section: Perspectivessupporting
confidence: 87%
“…In other words, the present subjects reached their limit in improving their neuromuscular performance with the poweronly training protocol utilized in this investigation. Previous studies (Lyttle et al, 1996;Newton et al, 2002) have suggested that heavy resistance strength training together with power training may better affect improvements in performance than power training alone. Newton et al (2002) demonstrated that mixed-methods resistance-training increased both muscle strength and power, while Lyttle et al (1996) found that a combination of plyometric and weight training was superior in comparison with ballistic resistance training for increasing jumping performance.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, BMR-induced stair climbing time reductions were higher in this group and power increased more in elderly female subjects with respect to the other subjects, therefore indicating that the adaptive capacity of stair climbing performance was superior in individuals with low initial values (see also below). Previous research demonstrated similar improvements in whole muscle characteristics among elderly men and women 25,26 and among young and old nonobese subjects 27,28 following resistance training protocols. However, little is known on the differential adaptability of elderly male vs female or young vs old obese subject and for the first time, the present study demonstrated that older obese women increased power more than their male and young counterparts.…”
Section: Stair Climbing Power In Obese Patientsmentioning
confidence: 63%
“…Em outras pesquisas (SCHLICHT et al, 2001;SCHOT et al, 2003), os resultados também foram expressivos. Newton et al (2002) verificaram os efeitos de um programa de treinamento contra resistência no período de 10 semanas. Nesse programa, foi manipulada, entre outras variáveis, a força máxima.…”
Section: Resultsunclassified